Pemanfaatan Limbah Ternak Sapi Berdasarkan Alternatif Distribusi Potensi Biogas Desa Pudak Wetan, Kabupaten Ponorogo - Faza, Winda Rosyida; Meidiana, Christia; Dwi Ari, Ismu Rini (Jurnal Tata Kota dan Daerah, 2013)
Pudak Wetan is the name of a village in Ponorogo which has a Livestock Center (RTRW Ponorogo 2010-2013). So that Pudak Wetan has an alternative energy resource for cooking, in the form of cow manure potency with the ownership of ±2-4 cows/breeder. But in fact, there’s just 8,8% of 329 breeders who can manage their waste to make it into biogas with the biodigester. Operational requirement of biodigester sized 6m Jurnal Tata Kota dan Daerah Volume 5, Nomor 2, Desember 2013 109 3 is every farmer has at least 2 adult cows. Gas production can be used for 7 hours of cooking time, but every farmer to use gas only for 3-4 hours. There are only 5 of the 29 breeders who utilize biogas communally because of family connections. Another problem is very hard to realize the centrality into the village scale because of the settlement and the topography. Therefore the primary aim of this research is to identify the best alternative to distribute the cow manure potency and then the best alternative is used as a reference division of the breeders group based on spatial and statistical characteristics.This paper use some methods for analising, there are multicriteria analysis, spatial cluster analysis, and statistic cluster analysis. There are four variabels in this research are location, economic, social, and technical. The result of this research shows that the best alternative of the biodigester’s type is the medium scale for 2-5 breeders with 10-25 cows. In this system, there are 25 groups for breeders which is the maximum size is 22m 3 for 5 breeders and the minimum size is 6mKeywords : Biogas, Cow Manure , Biodigester , Alternative Distribution of Biogas